Pengembangan Teknologi ERP Modul Accounting Management Studi Kasus: Anton Aluminium - Muhammad Arif Ilhamnoor; Depi Rusda (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2020)
The use of technology is expected to provide great benefits to the competitive business world. Companies that are able to compete in this competition are companies that are able to implement technology into their companies. One type of technology implementation in terms of increasing business competition is to use an Enterprise Resource Planning, or ERP system, in which there are several modules, one of which is the accounting management module. Anton Aluminum is a business place that is engaged in the sale of household furniture such as cabinets made of aluminum. At the beginning of the business, the owner did the marketing of his goods by mouth, for now the sales system used by the company is still manual or written. The problem that occurs with Anton Aluminum is that there are often errors in data processing and the preparation of monthly reports still requires a lot of time and accuracy, resulting in frequent delays in presenting information. To solve this problem, we need an accounting management system. Where later it can process financial transaction data, present financial data reports including journal reports, ledger reports, trial balance reports and income statements. In building this application program, using PHP and Javascript as a programming language media and MySQL is used as database management. This system is expected to make it easier for Anton Aluminum to record transactions and financial reports.